2007
DOI: 10.1157/13112988
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Levels and Lipid Profiles in Patients with Allergic Rhinitis and Mild Asthma

Abstract: Our data demonstrate that the serum levels of leptin and lipid profiles on allergic rhinitis and mild asthma were not different than those in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…Although prior studies have also assessed the relationship between serum HDL-C and asthma, the results have been heterogeneous with serum HDL-C levels either being increased, decreased, or unchanged in subjects with asthma (20,(43)(44)(45)(46)(47)(48)(49)(50). Similar to our findings, prior studies have also not found a change in serum LDL-C in subjects with asthma, whereas TC was either decreased or unchanged and TG levels were either increased or unchanged.…”
Section: Discussionsupporting
confidence: 80%
“…Although prior studies have also assessed the relationship between serum HDL-C and asthma, the results have been heterogeneous with serum HDL-C levels either being increased, decreased, or unchanged in subjects with asthma (20,(43)(44)(45)(46)(47)(48)(49)(50). Similar to our findings, prior studies have also not found a change in serum LDL-C in subjects with asthma, whereas TC was either decreased or unchanged and TG levels were either increased or unchanged.…”
Section: Discussionsupporting
confidence: 80%
“…In fact, a first study reported that serum leptin levels were found to be significantly higher in patients with allergic rhinitis in the symptomatic period than normal controls (Unal, 2006). A next study demonstrated that the serum levels of leptin on allergic rhinitis were not different than in controls (Erel, 2007). However, both studies did not consider the type of sensitization, the gender, and the age of patients, and the relationship between leptin and clinical parameters.…”
Section: Introductionmentioning
confidence: 95%
“…However, this association did not persist when clinical data, such as age, parental asthma and active smoking status, were included in the statistical model [105]. Other studies have found no correlation between serum leptin levels and asthma [106,107]. Altogether, evidence of a link between asthma and serum leptin remains unclear and further studies are needed to elucidate whether leptin directly participates in the pathogenesis of asthma, perhaps in certain subsets of this heterogeneous disease, or whether increased serum leptin levels are merely the result of the systemic inflammation that accompanies both asthma and obesity.…”
Section: Role Of Leptin In Inflammatory Lung Diseasesmentioning
confidence: 99%